Barrios en la ciudad de Alajuela como lugares del relato - Barrantes, Celia (2013)
Neighborhoods in the city of Alajuela are reservoirs of a particular every day life that gives identity to his inhabitants and the public space, and that is being built in the present time through the staging of the stories of those who live it now.